The Clinician-Educator's Handbook - Teri Turner; Debra Palazzi; Mark Ward; Martin Lorin (Association of American Medical Colleges, 2010)
Abstract Introduction The Clinician-Educator's Handbook addresses a wide variety of issues in clinical education and looks at many different settings in which clinical teaching takes place. The ultimate goal of clinical teaching is to improve patient care, and this handbook is designed to help the clinician-educator do the best possible job of teaching. Culling the literature on educational psychology and medical education, and drawing from their own observations and experiences, as well as those of many renowned clinician-teachers whom they observed and interviewed, the authors have created a physician-friendly work, written in the language of the clinician rather than of the educational theorist. Methods This resource contains a 20 chapter book on how to conduct clinical teaching. Chapters are arranged by topics ranging from designing the educational experience to bedside teaching to leading a case discussion. An instruction guide explaining how to best use the resource is also provided. Results Numerous personal communications have been received by the authors describing the usefulness to clinician-educators. The website has received over 1600 hits over a 9-month period. Discussion The Clinician-Educator's Handbook addresses a wide variety of issues of clinical education and looks at many different settings in which clinical teaching takes place The authors acknowledge that they have neither the experience nor the expertise to address issues involved in teaching surgical skills or in teaching in certain environments such as the operating room or the intensive care unit, so these areas are not covered in this book. While the authors are pediatricians, they believe that this book will be of interest to all physicians who wish to improve their teaching skills and hope that all readers will find this book enlightening, challenging, and useful.